Solidify eutectic electrolytes via the added MXene as nucleation sites for a solid-state zinc-ion battery with reconstructed ion transport - Meng, Xiangxuan; Du, Mingdong; Li, Yuning; Du, Shiji; Zhao, Lixin; Zheng, Shunri; Zhang, Jian; Li, Haibo; Qiao, Liang; Tan, Kar Ban; Han, Wenjuan; Xu, Shichong; et al. (American Chemical Society, 2024)
Stationary energy storage infrastructure based on zinc-ion transport and storage chemistry is attracting more attention due to favorable metrics, including cost, safety, and recycling feasibility. However, splitting water and liquid electrolyte fluidity lead to cathode dissolution and Zn corrosion, resulting in rapid attenuation of the capacity and service life. Herein, a new architecture of solid-state electrolytes with high zinc ionic conductivity at room temperature was prepared via solidification of deep eutectic solvents utilizing MXene as nucleation additives. The ionic conductivity of MXene/ZCEs reached 6.69 × 10−4 S cm−1 at room temperature. Dendrite-free Zn plating/stripping with high reversibility can remain for over 2500 h. Subsequently, the fabricated solid-state zinc-ion battery with eliminated HER and suppressed Zn dendrites exhibited excellent cycling performance and could work normally in a range from −10 to 60 °C. This design inspired by eutectic solidification affords new insights into the multivalent solid electrochemistry suffering from slow ion migration.